Epidemiology of Human Parainfluenza Virus Type 3 and Respiratory Syncytial Virus Infections in the Time of Coronavirus Disease 2019: Findings From a Household Cohort in Maryland. (12th December 2022) - Hetrich, Marissa K; Oliva, Jennifer; Wanionek, Kimberli; Knoll, Maria Deloria; Lamore, Matthew; Esteban, Ignacio; Veguilla, Vic; Dawood, Fatimah S; Karron, Ruth A; ,
Abstract: Background: During the coronavirus disease 2019 (COVID-19) pandemic, human parainfluenza type 3 (HPIV-3) and respiratory syncytial virus (RSV) circulation increased as nonpharmaceutical interventions were relaxed. Using data from 175 households (n = 690 members) followed between November 2020 and October 2021, we characterized HPIV-3 and RSV epidemiology in children aged 0–4 years and their households. Methods: Households with ≥1 child aged 0–4 years were enrolled; members collected weekly nasal swabs (NS) and additional NS with respiratory illnesses (RI). We tested NS from RI episodes in children aged 0–4 years for HPIV-3, RSV, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) using reverse-transcriptase polymerase chain reaction (RT-PCR). Among children with HPIV-3 or RSV infection, we tested contemporaneous NS from household members. We compared incidence rates (IRs) of RI with each virus during epidemic periods and identified household primary cases (the earliest detected household infection), and associated community exposures. Results: 41 of 175 (23.4%) households had individuals with HPIV-3 (n = 45) or RSV (n = 46) infections. Among children aged 0–4 years, RI IRs /1000 person-weeks were 8.7 [6.0, 12.2] for HPIV-3, 7.6 [4.8, 11.4] for RSV, and 1.9 [1.0, 3.5] for SARS-CoV-2. Children aged 0-4 years accounted for 35 of 36 primary HPIV-3 or RSV cases. Children attending childcare or preschool had higher odds of primary infection (odds ratio, 10.81; 95% confidence interval, 3.14–37.23). Conclusions: Among children aged 0–4 years, RI IRs for HPIV-3 and RSV infection were 4-fold higher than for SARS-CoV-2 during epidemic periods. HPIV-3 and RSV were almost exclusively introduced into households by young children. Abstract : We examined human parainfluenza type 3 and respiratory syncytial virus infections during the coronavirus disease 2019 pandemic and identified risk factors for introduction into households. Most primary household cases were children aged 0–4 years and attended childcare or preschool.